Experimental and numerical research on jet dynamics of cavitation bubble near dual particles - Yuning Zhang; Xuan Lu; Jinsen Hu; Jiaxin Yu; Yuning Zhang (Ultrasonics Sonochemistry)
The current paper delves into the jet dynamics arising from a cavitation bubble in proximity to a dual-particle system, employing both experimental methodology and numerical simulation. The morphological development of a laser-induced bubble as well as the production of jets are captured by utilizing high-speed photography. The principles of bubble morphology evolution and jet formation are revealed by a OpenFOAM solver, which takes into account the effects of two-phase fluid compressibility, phase changes, heat transfer, and surface tension. Fluid temperature variations induced by bubble oscillations are discussed. The results indicate that the jet dynamics can be categorized into three cases, i.e. bubble-splitting double jets, impacting single jet, non-impacting double jets. For bubble-splitting double jets, bubble splitting is induced by an annular pressure gradient towards the bubble axis. This resulted in the production of two unequal-sized sub-bubbles, which subsequently produced double jets in opposite directions. The fluid temperature close to the bubble interface is low, while the bubble center is high. For impacting single jet, it is induced by a conical pressure gradient towards the nearest particle and the jet impacts the particle. The fluid temperature is low near the jet and high near the particle. When the jet penetrates the bubble interface, the temperature inside the bubble reaches its peak. For non-impacting double jets, they are induced by pressure gradients facing each other and they do not impact particles. The temperature inside the bubble increases with the proximity of the two jets.